PENGARUH EMPLOYER BRAND IMAGE TERHADAP INTENSI MELAMAR PEKERJAAN DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL MODERASI (Studi pada Pencari Kerja Generasi Y) - Lathofany Budiono, Alya; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2021)
The retirement wave of Baby Boomer’s is placing industry at risk of labor shortages for the next few years. This results in severe competition between companies for attracting and retaining potential young workforces to be developed as superior successors. Hence, the concept of employer brand emerges as an element of company strategy to attract and retain potential candidates from the labor market. Although many companies in Indonesia have implemented employer branding strategies to attract and retain potential workforce, there is still a limited amount of research related to this concept in Indonesia.            Thus, this research aims to determine and analyze the effects of employer brand image on intent to apply for a job with work experience as a moderator among a sample of Generation Y Job Seekers. The population in this research is Diponegoro University Graduates that were seeking for employment at the time of participation. The sample consists of 105 Job Seekers.            Data in this research was collected through distribution of questionnaires using non-probability sampling technique with purposive sampling methods. Each item in the questionnaire is measured by five-point likert scale.             The results of this research showed that employer brand image is proved to give positive and significant effect on intent to apply for a job. In addition, the results also showed that work experience didn’t moderate the relationship between employer brand image and intent to apply.